Scientific and educational aspects of the EEE Project. (June 2020) - La Rocca, P.; Abbrescia, M.; Avanzini, C.; Baldini, L.; Baldini Ferroli, R.; Batignani, G.; Battaglieri, M.; Boi, S.; Bossini, E.; Carnesecchi, F.; Cicalò, C.; Cifarelli, L.; et al.
Abstract: The Extreme Energy Events (EEE) Project is an experiment aimed at the detection of secondary cosmic ray muons. It consists of a sparse array of about 60 telescopes, based on Multigap Resistive Plate Chambers (MRPCs), mostly distributed throughout the Italian territory, mainly in high schools locations, and at CERN. The telescopes are now operational and taking data since more than ten years with a high duty cycle and detection efficiency. The analysis activity is currently in progress and focused on several items, including the detailed study of the muon ux under dfferent conditions, its connection with atmospheric and solar events, the detection of extensive air showers and the search for long distance correlations between different extensive air showers. In this paper an overall description of the experiment will be given, together with its educational fallout. The operation of the whole array is also discussed by showing the most recent results obtained from the analysis of the collected data.